Score of Elis Regina's performance in Atrás da porta, by Chico Buarque and Francis Hime (Per Musi, 2014)
"Atrás da Porta" according to lead sheet edited by Almir Chekiak and Elis Regina's recording in the video Na Batucada da Vida (1973).